2018
DOI: 10.1002/jcp.27236
|View full text |Cite
|
Sign up to set email alerts
|

8‐Br‐cADPR, a TRPM2 ion channel antagonist, inhibits renal ischemia–reperfusion injury

Abstract: The transient receptor potential melastatin-2 (TRPM2) channel belongs to the transient receptor potential channel superfamily and is a cation channel permeable to Na and Ca . The TRPM2 ion channel is expressed in the kidney and can be activated by various molecules such as hydrogen peroxide, calcium, and cyclic adenosine diphosphate (ADP)-ribose (cADPR) that are produced during acute kidney injury. In this study, we investigated the role of 8-bromo-cyclic ADP-ribose (8-Br-cADPR; a cADPR antagonist) in renal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 78 publications
(124 reference statements)
1
24
0
3
Order By: Relevance
“…It is worth noting that inhibitors identified in earlier studies, including 2-aminoethoxydiphenyl borate (2-APB), N-( p -amycinnamoyl) anthranilic acid (ACA), antifungal agents such as clotrimazole (CTZ) and econazole and the non-steroidal anti-inflammatory flufenamic acid (FFA), while inhibiting the TRPM2 channel with concentrations producing a 50% inhibition (IC 50 ) in the range of μM ( Table 2 ) [ [106] , [107] , [108] , [109] , [110] , [111] ], lack specificity towards the TRPM2 channel [ 73 ]. 8-Br-cADPR, an ADPR analogue, is reported to inhibit the TRPM2 channel by in vitro [ 62 ] and also in vivo studies [ 112 ] but, of notice, its inhibition has not been consistently observed [ 113 ]. Recent studies have tested various other ADPR-related analogues for their potential to selectively inhibit the TRPM2 channel in vitro [ 114 , 115 ], identifying multiple compounds such as 8-phenyl-2′-deoxy-ADPR, 7i and 8a ( Table 2 ).…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that inhibitors identified in earlier studies, including 2-aminoethoxydiphenyl borate (2-APB), N-( p -amycinnamoyl) anthranilic acid (ACA), antifungal agents such as clotrimazole (CTZ) and econazole and the non-steroidal anti-inflammatory flufenamic acid (FFA), while inhibiting the TRPM2 channel with concentrations producing a 50% inhibition (IC 50 ) in the range of μM ( Table 2 ) [ [106] , [107] , [108] , [109] , [110] , [111] ], lack specificity towards the TRPM2 channel [ 73 ]. 8-Br-cADPR, an ADPR analogue, is reported to inhibit the TRPM2 channel by in vitro [ 62 ] and also in vivo studies [ 112 ] but, of notice, its inhibition has not been consistently observed [ 113 ]. Recent studies have tested various other ADPR-related analogues for their potential to selectively inhibit the TRPM2 channel in vitro [ 114 , 115 ], identifying multiple compounds such as 8-phenyl-2′-deoxy-ADPR, 7i and 8a ( Table 2 ).…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…Such kidney damage and loss of function in WT mice were also reduced in mice injected with 2-APB prior to ischemia or after reperfusion. A more recent study has reported that I/R-induced kidney damage examined histologically using H&E staining in WT mice was prevented by treatment with 8-Br-cADPR to antagonise TRPM2 channel activation [ 112 ]. These studies provide consistent evidence to support an important role for the TRPM2 channel in I/R-induced acute kidney injury.…”
Section: Trpm2 In Kidney Cell Death Associated With Acute Kidney Injumentioning
confidence: 99%
“…Studies involving both abdominal and renal I/R models have reported that I/R causes apoptosis in renal tubule cells [11,27] . In their study using an aortic cross-clamping model in rats, Cüre et al [10] reported an increase in Caspase-3 positivity in apoptotic renal cells following I/R application.…”
Section: Discussionmentioning
confidence: 99%
“…Although organ reperfusion following ischemia may decrease the existing injury, it may adversely affect several cellular processes emerging due to the reperfusion. The severity of the injury may lead to organ dysfunctions [2,3]. Hypoxia, inflammatory cytokines, and free oxygen radicals are the underlying factors of the renal IRI.…”
Section: Introductionmentioning
confidence: 99%